From Policy Formulation to Educational Outcomes: A Holistic Governance Analysis of Islamic Education Policy in Indonesia - Achmad Jasuli Afandi; Muhammad Eko Arief Wijaksono; Abd. Muis (DAAR EL-MAKRIFAH: Journal of Islamic Religious Education, 2026)
Islamic Religious Education plays an important role in developing students’ moral, spiritual, and social character in Indonesia. This study aims to analyze the formulation, implementation, and future direction of IRE policy in Indonesia amid the challenges of globalization and digital transformation. The research employed a qualitative library research approach using government regulations, policy documents, academic books, and scholarly articles as data sources. Data were analyzed through content analysis and critical discourse analysis. The findings indicate that IRE policy has evolved from a state-centered approach toward a more collaborative and integrative model that combines religious values with scientific and technological developments. The implementation of IRE policy is influenced by teacher competence, institutional capacity, and digital readiness, while challenges remain in the form of educational disparities, policy fragmentation, and digital inequality. The study concludes that future reforms should emphasize integration-interconnection, collaborative governance, digital transformation, and Maqasid al-Shariah to strengthen the relevance and sustainability of Islamic education in the twenty-first century.